Stress-Induced Executive Dysfunction in GDNF-Deficient Mice, A Mouse Model of Parkinsonism - Buhusi, Mona; Olsen, Kaitlin; Yang, Benjamin Z.; Buhusi, Catalin V. (Frontiers in Behavioral Neuroscience, 2016)
Maladaptive reactivity to stress is linked to improper decision making, impulsivity, and discounting of delayed rewards. Chronic unpredictable stress alters dopaminergic function and re-shapes dopaminergic circuits in key areas involved in decision making, and impairs prefrontal-cortex dependent response inhibition and working memory. Glial-derived neurotrophic factor (GDNF) is essential for regulating dopamine release in the basal ganglia and the survival of dopaminergic neurons, and GDNF-deficient mice are considered an animal model for aging-related Parkinsonism. Recently, GDNF expression in the striatum has been linked to resilience to stress. Here we investigated the effects of chronic unpredictable stress on decision making in GDNF-heterozygous (HET) mice and their wild-type littermate controls (WT). Before chronic unpredictable stress no differences in temporal discounting were found between genotypes. However, following chronic unpredictable stress GDNF heterozygous mice, having a partial reduction of GDNF levels, showed increased impulsive choice indexed by a reduction in percent larger-later choices in the temporal discounting paradigm, and a reduction in area under the temporal discounting curve. Moreover, stressed GDNF-HET mice, but not their WT controls, showed decreased neuronal activation (number of cFos positive neurons) in the orbitofrontal cortex, nucleus accumbens core, and nucleus accumbens shell, suggestive of a maladaptive response to stress. Interestingly, area under the temporal discounting curve positively correlated with cFos activation in the nucleus accumbens core, and nucleus accumbens shell, but not with orbitofrontal activity. These results provide further evidence of the differential involvement of the orbital frontal cortex, nucleus accumbens core, and nucleus accumbens shell in impulsive choice, and identify GDNF-deficient mice as a double-hit (gene x environment) model of stress-related executive dysfunction, particularly relevant to substance abuse and Parkinson’s Disease.